Free to Consume? Anti-Paternalism and the Politics of New York City's Soda Cap Saga. (7th January 2017) - Bateman-House, Alison; Bayer, Ronald; Colgrove, James; Fairchild, Amy L; McMahon, Caitlin E
Abstract: In 2012, New York City Mayor Michael Bloomberg proposed capping the size of sugary beverages that could be sold in the city's restaurants, sporting and entertainment facilities and food carts. After a lawsuit and multiple appeals, the proposal died in June 2014, deemed an unconstitutional overreach. In dissecting the saga of the proposed soda cap, we highlight both the political perils of certain anti-obesity efforts and, more broadly, the challenges to public health when issues of consumer choice and the threat of paternalism are involved.